Introducing Water‐Network‐Assisted Proton Transfer for Boosted Electrocatalytic Hydrogen Evolution with Cobalt Corrole. Issue 9 (4th January 2022) - Li, Xialiang; Lv, Bin; Zhang, Xue‐Peng; Jin, Xiaotong; Guo, Kai; Zhou, Dexia; Bian, Hongtao; Zhang, Wei; Apfel, Ulf‐Peter; Cao, Rui
Abstract: Proton transfer is vital for many biological and chemical reactions. Hydrogen‐bonded water‐containing networks are often found in enzymes to assist proton transfer, but similar strategy has been rarely presented by synthetic catalysts. We herein report the Co corrole 1 with an appended crown ether unit and its boosted activity for the hydrogen evolution reaction (HER). Crystallographic and 1 H NMR studies proved that the crown ether of 1 can grab water via hydrogen bonds. By using protic acids as proton sources, the HER activity of 1 was largely boosted with added water, while the activity of crown‐ether‐free analogues showed very small enhancement. Inhibition studies by adding 1) external 18‐crown‐6‐ether to extract water molecules and 2) potassium ion or N ‐benzyl‐n‐butylamine to block the crown ether of 1 further confirmed its critical role in assisting proton transfer via grabbed water molecules. This work presents a synthetic example to boost HER through water‐containing networks. Abstract : A cobalt corrole with an appended crown ether unit was designed and synthesized to model water‐network‐assisted proton transfer as found in metalloproteins. Experimental and theoretical studies confirmed that the crown ether unit of this cobalt corrole can grab water molecules through hydrogen bond interactions and the established water network plays vital roles in assisting proton transfer, leading to significantly boosted electrocatalytic HER activity.